First Report of Pratylenchoides leiocauda parasitic on Perilla frutescenes in the Republic of Korea - Kang, Heonil; Ko, Hyoung-Rai; Park, Byeongyong; Park, Sekeun; Park, Eunhyeong; Kim, Eunhwa (Plant disease, 2023)
Perilla ( (L.) Britton ) is an annual herbaceous crop belonging to Lamiaceae. It is one of the most important crops in Korea. A survey of plant parasitic nematodes was carried out in 70 perilla fields in Geumsan and Miryang, Korea in 2020. Migratory endo-parasitic nematodes were extracted from the perilla roots using modified root incubation methods (Mountain and Patrick, 1959). False root-lesion nematodes ( ) were recovered from 41.4% of the fields. They were identified using morphological and molecular analyses. Among the species, was described in France from soil around non-identified grass and weeds. is reported to weaken the root systems of tomato, potato and strawberry (Sher, 1970; Li et al., 2020). The morphological characteristics of males and females from the 2020 survey were very similar to . The lateral field contained six incisures and the pharyngeal glands overlapped the intestine dorsally for 1-2 times the body width. Additionally, they had a second nucleus near the pharyngeal intestine valve, female tails with incisures, and a smooth conical tail with 18-23 annules. Measurements and micrographs with the light-microscope (DM5000, Leica, Germany) and camera (DFC450, Leica, Germany) were taken from females (n=23) for mean, standard deviation and range of body length: 824.5 ± 71.0 (657.7-993.8) µm, maximum body width: 28.4 ± 2.7 (24.8-36.2) µm, stylet length: 22.8 ± 0.7 (21.4-24.0) µm and percent of distance from anterior end to vulva / body length: 57.7 ± 1.4 (54.0-60.3). Males (n=5) were characterized by a body length: 653.5 ± 64.3 (555.3-714.7) µm, a stylet length: 20.9 ± 1.0 (19.7-22.0) µm and a spicule length: 26.1 ± 2.5 (22.3-28.5) µm. Morphological measurements and characteristics (Fig. 1A-F) were compared to previous descriptions of . As a result, the Korean population was larger than that of the originally described population from France, and was more similar to the Chinese population (Sher, 1970; Azizi et al., 2016; Li et al., 2020). In addition, PCR was performed for the Ⅰ, LSU rRNA D2-D3 and ITS region using the primers (Mwesige et al., 2020). The sequenced Ⅰ, LSU rRNA D2-D3 segments and ITS region are 447, 776 and 777 bp, respectively. The newly obtained sequences were submitted to GenBank database under accession numbers MZ418130, MZ414163 and MZ418133 of ITS region. A BLASTn search of the LSU rRNA D2-D3 sequence was most similar to (MN539650), which is the species isolated from tomato in China (Li et al., 2020). The identities of these two sequences were 99.9% (775/776), with no insertions/deletions. The phylogenetic relationships strongly support (Fig. 1G). Symptoms of perilla associated with under field conditions included small and curled leaves, chlorosis of leaf edges, dark brown root epidermis and root necrosis (Fig. 2A, B). Koch's postulates were completed by inoculating 100 into ten 45-cm-in-diameter pots filled with sterilized sandy loam soil and planted with perilla cultivar 'Ipdeulkkae 1-ho'. The potted plants were maintained for 50 days at 25℃ under greenhouse conditions. A reproduction factor was 1.45 ± 0.20 was observed at the end of the trial, with 106 ± 21.6 recovered from soil and 39 ± 6.7 from root tissue. The root and shoot symptoms in the greenhouse trial were the same as those observed under field conditions (Fig. 2C, D). This, therefore, is the first record of associated with perilla in Korea and management is warranted.